Quantification of the strong, phonon-induced Urbach tails in β-Ga2O3 and their implications on electrical breakdown - Islam, Ariful; Rock, Nathan David; Scarpulla, Michael A. (Journal of applied physics, 2024)
In ultrawide bandgap (UWBG) nitride and oxide semiconductors, increased bandgap (Eg) correlates with greater ionicity and strong electron–phonon coupling. This limits mobility through phonon scattering, localizes carriers via polarons and self-trapping, broadens optical transitions via dynamic disorder, and modifies the breakdown field. Herein, we use polarized optical transmission spectroscopy from 77 to 633 K to investigate the Urbach energy (Eu) for many orientations of Fe- and Sn-doped β-Ga2O3 bulk crystals. We find Eu values ranging from 60 to 140 meV at 293 K and that static (structural defects plus zero-point phonons) disorder contributes more to Eu than dynamic (finite temperature phonon-induced) disorder. This is evidenced by lack of systematic Eu anisotropy, and Eu correlating more with x-ray diffraction rocking-curve broadening than with Sn-doping. The lowest measured Eu are ∼10× larger than for traditional semiconductors, pointing out that band tail effects need to be carefully considered in these materials for high field electronics. We demonstrate that, because optical transmission through thick samples is sensitive to sub-gap absorption, the commonly used Tauc extraction of a bandgap from transmission through Ga2O3 >1–3 μm thick is subject to errors. Combining our Eu(T) from Fe-doped samples with Eg(T) from ellipsometry, we extract a measure of an effective electron–phonon coupling that increases in weighted second order deformation potential with temperature and a larger value for E||b than E||c. The large electron–phonon coupling in β-Ga2O3 suggests that theories of electrical breakdown for traditional semiconductors need expansion to account not just for lower scattering time but also for impact ionization thresholds fluctuating in both time and space.